Social role theory as a means of differentiating between first-generation and non-first-generation college students - Hemphill, Leslie L. (Kansas State University, 2008)
Statistics published in 2003 indicate that over 67% of community college students are first-generation students, students from families where neither parent has graduated from college. First-generation students are disproportionately represented among those who terminate college prior to graduation. This study explores role theory as a model for understanding and addressing the problems of first-generation students. Survey questions linked to role commitment involving intentions to work, commute and participate in campus activities were administered to 257 first-time full-time students: 182 students were first-generation and 75 were non-first-generation. Analysis using the Mann-Whitney U Test indicated first-generation students had significantly less commitment to the role of student. Later, first-generation students were divided into "successful" and "unsuccessful" groups based on their two semester grade point average. The Mann-Whitney U Test failed to demonstrate a significant difference between "successful" and "unsuccessful" first-generation students. The ordinal score responses of first-generation students to the three survey questions were then used as categories and grade point averages of the students in those categories were compared using ANOVA procedures. The results were mixed but suggested further investigation was warranted. The study was concluded with interviews of ten "successful" first-generation students. The interview results were supportive of conclusions drawn from role theory underscoring the value of further studies with larger sample sizes and modifications in methodology suggested by this study.
Keywords: First-Generation; Social Role Theory; Education, Guidance and Counseling (0519)